Réponses

2013-05-03T13:16:23+02:00

y+16-2*y*16-y²-10y

y-42y-y²+16

41y-y²+16

 

E=16

 

41y-y²+16=0

41y-y²=-16

y-y²=-16/41

 

 
2013-05-03T13:17:29+02:00

Bonjour,

a)

 

1)E = \left(y-4\right)^2-y\left(y-10\right)\\ E = y^2-8y+16-\left(y^2-10y\right)\\ E = y^2-8y+16-y^2+10y\\ E = 2y+16

 

2)2y+16 = 16\\ 2y = 0\\y=0

 

b)F = \left(7y-3\right)^2-5^2\\ F = \left(7y-3+5\right)\left(7y-3-5\right)\\ F = \left(7y+2\right)\left(7y-8\right)

 

Si un produit est nul, alors l'un au moins de ses facteurs est nul, donc :

7y+2 = 0\\ 7y = -2 \\y = -\frac 27

 

Ou

 

7y-8 = 0 \\7y = 8 \\y =\frac 87